The Leishmania donovani LDBPK_220120.1 Gene Encodes for an Atypical Dual Specificity Lipid-Like Phosphatase Expressed in Promastigotes and Amastigotes; Substrate Specificity, Intracellular Localizations, and Putative Role(s) - Papadaki, Amalia; Tziouvara, Olympia; Kotopouli, Anastasia; Koumarianou, Petrina; Doukas, Anargyros; Rios, Pablo; Tardieux, Isabelle; Köhn, Maja; Boleti, Haralabia (Frontiers in Cellular and Infection Microbiology, 2021)
The intracellular protozoan parasites of the Leishmania genus are responsible for Leishmaniases, vector borne diseases with a wide range of clinical manifestations. Leishmania (L.) donovani causes visceral leishmaniasis (kala azar), the most severe of these diseases. Along their biological cycle, Leishmania parasites undergo distinct developmental transitions including metacyclogenesis and differentiation of metacyclic promastigotes (MPs) to amastigotes. Metacyclogenesis inside the phlebotomine sandfly host’s midgut converts the procyclic dividing promastigotes to non-dividing infective MPs eventually injected into the skin of mammalian hosts and phagocytosed by macrophages where the MPs are converted inside modified phagolysosomes to the intracellular amastigotes. These developmental transitions involve dramatic changes in cell size and shape and reformatting of the flagellum requiring thus membrane and cytoskeleton remodeling in which phosphoinositide (PI) signaling and metabolism must play central roles. This study reports on the LDBPK_220120.1 gene, the L. donovani ortholog of LmjF.22.0250 from L. major that encodes a phosphatase from the “Atypical Lipid Phosphatases” (ALPs) enzyme family. We confirmed the expression of the LDBPK_220120.1 gene product in both L. donovani promastigotes and axenic amastigotes and showed that it behaves in vitro as a Dual Specificity P-Tyr and monophosphorylated [PI(3)P and PI(4)P] PI phosphatase and therefore named it LdTyrPIP_22 (Leishmaniad onovani Tyrosine PI Phosphatase, gene locus at chromosome 22). By immunofluorescence confocal microscopy we localized the LdTyrPIP_22 in several intracellular sites in the cell body of L. donovani promastigotes and amastigotes and in the flagellum. A temperature and pH shift from 25°C to 37°C and from pH 7 to 5.5, induced a pronounced recruitment of LdTyrPIP_22 epitopes to the flagellar pocket and a redistribution around the nucleus. These results suggest possible role(s) for this P-Tyr/PI phosphatase in the regulation of processes initiated or upregulated by this temperature/pH shift that contribute to the developmental transition from MPs to amastigotes inside the mammalian host macrophages.